Penyebaran Konsentrasi Polutan Dengan Pemodelan Dispersi Gauss Menggunakan Matlab - Jainal Abidin; Ferawati Artauli Hasibuan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
In the era of development of science and technology until 2019 it has become increasingly sophisticated and makes life easier for humans. This progress has led to increasingly sophisticated technology with the intention of making life easier, practical, efficient and not experiencing much difficulty. But the development of these technologies, have positive and negative impacts. Positive impacts such as convenience, while negative impacts such as air pollution. Contamination of pollutants into the air resulting from factory activities, power plants and motor vehicles spread to the environment. This substance is very damaging to the environment which causes the air we breathe to be polluted and very influential on health. This study aims to describe the process of spreading pollutant concentrations in the air originating from factory chimney fumes. Pollutants that spread in the air can be modeled with the dispersion gauss model which is processed using the MATLAB programming language. The expected results from modeling are the distance of the highest pollutant concentration area and the range of pollutant coverage that spread, so that later will be done variations of the effective height of the chimney emission (H) to get results that vary according to the height of the chimney.